Caracterização das vias neuro-humorais no retarde do esvaziamento gástrico de líquidos advindo da distensão mecânica atrial direita em ratos acordados - Palheta Júnior, Raimundo Campos (2010)
Right atrium mechanical stretch (AS) increases gastric motility in anesthetized rats. We aimed to study the effect of AS on gastric emptying (GE) in awake rats and the related neuro-humoral pathways ivolved. Male albino rats (N=361, 250-280g) had a silicone balloon inserted in the right atrium. After 24-h, the central venous pressure (CVP), heart rate (HR) and the mean arterial pressure (MAP) were monitored and after the initial 20-min, animals were randomly pre-treated with: saline (S, 0.1 ml/100g, i.v.), Atropine (A, 0.5mg/kg, i.v.), Guanethidine (GT, 10mg/kg, i.p.), hexamethonium (H, 10mg/kg, i.v.), L-NAME (3mg/kg, i.v.), L-Arginine (100mg/kg, i.v.)+L-NAME (3mg/kg, i.v.), Methylene Blue (MB, 3mg/kg, i.v.), Glibenclamide (GB, 1mg/kg, i.p) or Glibenclamide+Diazoxide (3mg/kg, i.v.) [GB+D], Dexamethazone (DEX, 1mg/kg, i.p.), Anantin (ANT, 5g, i.v.) or Atosiban (AT, 40g/kg/h, i.v.). Besides, in a separate group, we realized vagotomy (V), or splanchnotomy + celiac gangliectomy (SC) or afferent cardiac denervation with capsaicin (ACD) 72h before AS. In another set of animals, we realized right appendectomy (AX) one week before AS. Next, AS with saline zero (sham) or 50L was performed during 5min. In this group, rats were gavage fed with a test meal 20-min after AS and euthanized 10-min afterwards to study GE. Moreover we determined plasmatic levels of Ocytocin (OT), Atrial Natriuretic Peptide (ANP) and Corticosterone (CORT), and determined the neuronal activity in the paraventricular (PVN) or supraoptic (SON) hypothalamic regions by measuring expressed double-labeled c-fos-OT. Comparing to Sham, AS decreased GE (p<0.05). Besides, AS increased CVP and HR. AS decreased GE (p <0.05) in S, A, GT, L-Arginine+L-NAME, MB and GB+D groups. However pre-treatment with, H, L-NAME, GB, DEX, ANT or AT, as well as SV, SC, ACD or AX prevented the effect of AS on GE. AS increased OT and CORT plasmatic levels, but did not alter ANP. In spite of AS increasing the number of c-fos expressing neurons in the parvocellular region, we did not observe this finding in the magnocellular regions of PVN or SON. Besides, AS did not alter the number of fos-OT double-labeled neurons. Therefore the decrease of GE of fluids after AS in awake rats depends on an afferent pathway mediated by cardiac low pressure receptors, and both sympathetic and parasympathetic neurons participate in the cascade mediated by OT, ANP and NO through K +-ATP dependent channels.